Elevated serum polyclonal immunoglobulin free light chains in patients with severe asthma - Basile, Umberto; Santini, Giuseppe; Napodano, Cecilia; Macis, Giuseppe; Pocino, Krizia; Gulli, Francesca; Malerba, Mario; Bush, Andrew; Adcock, Ian M.; Montuschi, Paolo (Frontiers in Pharmacology, 2023)
Background: Inflammation plays a pivotal role in the pathophysiology of asthma. Free light chains (FLC) can cause inflammation by mast cell antigen-activation. Serum immunoglobulin (Ig) FLC κ, but not λ, were shown elevated in adult males with asthma. We sought to investigate if serum Ig FLC concentrations are affected by asthma severity and their relationships with inflammatory outcomes. Methods: By using immunoassays, we measured serum κ and λ Ig FLCs in 24 severe persistent asthma patients, 15 patients with moderate persistent asthma, 15 steroid-naïve mild persistent asthma patients and 20 healthy control subjects in a cross-sectional observational study. Total and specific serum IgE concentrations, fractional exhaled nitric oxide (FENO), lung function, peripheral blood eosinophils and neutrophils, and C reactive protein (CRP) were also measured. Results: Serum κ FLC concentrations were elevated in severe asthma patients compared mild asthma patients (p < 0.05) and healthy subjects (p < 0.05). Serum λ FLCs were higher in severe asthma patients than in healthy subjects (p < 0.05) and correlated with blood eosinophil counts (percentage, κ: r = 0.51, p = 2.9678−6; λ: r = 0.42, p = 1.7377−4; absolute values, κ: r = 0.45, p = 6.1284−5; λ: r = 0.38, p = 7.8261−4), but not with total or specific serum IgE. In severe asthma patients, serum Ig FLC correlated with serum CRP (κ: r = 0.33; p = 0.003; λ: r = 0.38, p = 8.8305−4) and blood neutrophil cell counts (percentage, κ: r = 0.31; p = 0.008; λ: r = 0.29, p = 0.01; absolute values, κ: r = 0.40; p = 3.9176−4; λ: r = 0.40, p = 4.5479−4), were elevated in subjects with blood eosinophilia (≥300 cells/µL) (n = 13) compared with non-eosinophilic subjects (n = 10) (κ: 19.2 ± 1.2 mg/L versus 12.1 ± 1.3 mg/L, p < 0.001; λ: 27.2 ± 2.6 mg/L versus 16.8 ± 2.5 mg/L, p < 0.01), but were similar in atopic (n = 15) versus nonatopic subjects (n = 9) (κ: p = 0.20; λ: p = 0.80). Serum FLC were negatively correlated with lung function tests, including forced expiratory volume in one second (FEV1) (κ: r = −0.33; p = 0.0034; λ: r = −0.33; p = 0.0035), and FEV1/forced vital capacity ratio (κ: r = −0.33; p = 0.0034; λ: r = −0.33; p = 0.0036). Conclusion: Serum Ig FLCs are elevated in severe asthma adults and might represent new surrogate markers of inflammation. The pathophysiological implications of these findings require further research. This study was approved by the ethics committee of the University Hospital Agostino Gemelli Foundation and Catholic University of the Sacred Heart (approval number P/1034/CE2012).